Evaluating the Readiness of Pakistani Academic Libraries for the Adoption of Artificial Intelligence and Emerging Technologies - Muhammad Yousaf Rashid; Muhammad Arif; Arshad Ahmad; Mamoona Akhtar; Dr. Naimat Ullah Shah; Dr. Ata ur Rehman (Indus Journal of Social Sciences, 2025)
Purpose: In this research, the authors endeavor to assess the preparedness of Pakistani academic libraries to embrace artificial intelligence (AI) and new technologies. With AI transforming information provision across the world, technological, organizational, financial, and human-resource preparedness is critical to libraries that intend to remain relevant in terms of service delivery and operational efficiency. Design/Methodology/Approach: The survey design used was a quantitative and cross-sectional survey that was used to collect information on 230 library professionals in both public and private academic institutions in Pakistan. The information about the demographic characteristics and five central dimensions of readiness, including technological infrastructure, staff competency, organizational readiness, financial capacity, and perceived benefits and challenges, was gathered with the help of a structured questionnaire. A descriptive statistics were applied to data, which entailed frequencies and percentages, to determine trends, gaps, and strong points. Findings: The results show the medium level of technological preparedness, good hardware, network stability, and the internet connection, yet scarce access to AI tools, cloud services, and frequent system updates. The competency of staff is revealed as one of the primary limitations because most professionals are not trained in AI, they do not know how to program and troubleshoot AI even being highly motivated to do it. The lack of operational structures is demonstrated by organizational readiness through supportive leadership and strategic intent, yet lack of the following structures, such as specific roles of AI or committees. The least prepared area is financial preparedness as majority of the libraries are operating with tight budgets and are not able to invest heavily in long term technology. In spite of them, respondents remain very optimistic about the future of AI to enhance service quality, efficiency, personalization, and research support. Originality/Value: This paper provides one of the most detailed evaluations of AI preparedness among Pakistani scholarly libraries, which combines the technological, human, organizational, and financial approaches. It also offers evidence-based lessons that will be able to inform institutional planning, policy formulation, and capacity-building initiatives with an aim to promote sustainable AI integration.